190k views
4 votes
X^2 plus 2y divideed by 2x plus 3z equal

User Danielkza
by
5.2k points

1 Answer

1 vote

Answer:

(x^2 plus 2y")

--------------------

2x(2x + 3)

Explanation:

Doing this problem correctly requires the application of "order of operations" rules. "x^2 plus 2y" actually means "(x^2 plus 2y"), and so your

x^2 plus 2y divided by 2x

comes out to:

(x^2 plus 2y")

--------------------

2x

If we now divide this result by "2x plus 3z," we get:

(x^2 plus 2y")

--------------------

2x

================

2x + 3

or:

(x^2 plus 2y")

--------------------

2x(2x + 3)

User TuomasR
by
5.8k points